Migration patterns of Blackbird Turdus merula in northern Italy: a morphological and capture–recapture approach. Issue 2 (3rd July 2018) - Fornasari, Luca; Gustin, M.; Carini, R.; Maselli, M.
ABSTRACT: Blackbirds in Italy are believed to be a breeding, passage and wintering bird. Wintering individuals that breed in northern Europe are thought to be different morphologically from individuals breeding in Italy. In this paper we test the hypothesis that, during post-breeding and pre-breeding migrations and the wintering season, longer-winged migrants and shorter-winged residents co-exist. Using ringing data from three stations in northern Italy, we fitted linear models to test whether wing length differs significantly between breeding individuals and individuals captured only during migration or winter. Then, with capture–recapture models, we estimated recapture probabilities for individuals with short or long wing lengths, in cold and warm seasons. Our results show that breeding individuals have shorter wings than those captured only during migration or wintering, and that individuals with long wings cannot be recaptured (and are absent from the population) during the breeding season. These effects, however, did not have the same intensity at the three ringing stations involved in the project, suggesting that Blackbird migration differs in extent and pattern between the three stations.